An Exploratory Study to Investigate the Implementation of Feynman Learning Method in a Physics Classroom Setting - Wea, Kristiana Nathalia; Dua, Yohanes Sudarmo; Elizabeth, Agustina (Universitas Negeri Semarang, 2023)
In order to explore alternative methods to learn physics effectively, this research was inspired by a fundamental question: how did famous physicists use to learn and/or teach physics? Are there any recipies suggested by these physicists which are still relevant and can be imitated and applied to physics learning in a today classroom? This research aims at exploring the impact of the implementation of Feynman learning method on students’ physics concepts understanding and describing their spontaneous responses about the implementation of this learning method afterwards. This research was an exploratory research conducted at one grade X science class of St. Gabriel Catholic Senior High School in Maumere city, Flores. Data regarding students’ understanding were collected through pre and post test questionnairres and their spontaneous responses were obtained through unstructured interview. The results of N-gain pretest and post test score was 0.49. Apart from few non-positive responses, students’ responses indicated that the method can encourage them to actively participate in the learning process, improve their communication skill, and train their abilities to explain things in simple ways. The results suggest that there was an improvement in students’ physics concepts understanding with a medium N-gain score and that this learning method is positively appreciated by the participants.